Chlorine gas hazardous material incident in Karachi, Pakistan: a clinical experience from an emergency department of a tertiary care hospital - Ali, Noman; Nadeemullah Khan,; Syed Mustahsan,; Sajid Ali,; Shahan Waheed,; Uzma Khan,; admin, (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the clinical characteristics, management and outcomes of patients presenting with chlorine gas exposure in an emergency setting. Method: The single-centre, retrospective cross-sectional study was conducted at the emergency department of Aga Khan University Hospital, Karachi, and comprised data of all patients who presented on March 06, 2020, due to acute chlorine gas exposure after a specific industrial accident. Demographic and clinical data was recorded from the medical record files. The association between risk factors and complications was explored. Data was analysed using SPSS 20. Results: There were 51 male patients with a mean age of 33.10+8.37 years. The most commonly affected organ system was respiratory 49(96%), with 43(84.3) having shortness of breath. Eye irritation was found in 44(86.3%) cases and the central nervous system was involved in 14(27.4%). Most of the patients were admitted from the emergency department 36(70%). Regarding treatment, 1(1.9%) patient each required invasive and non-invasive mechanical ventilation. Complications included toxic pneumonitis 3(5.9%) and pneumomediastinum 1(1.7%). No correlation was found between smoking and complications (p>0.05). Conclusion: Most patients showed complete resolution of symptoms after receiving supportive treatment, while complications was rare and there was no mortality. Key Words: Chlorine gas, HAZMAT incident, Emergency department.